Alterations of the CxxC domain preclude oncogenic activation of mixed-lineage leukemia 2 - Bach, Christian; Mueller, D.; Buhl, Sebastian; Garcia-Cuellar, Maria-Paz; Slany, Robert (Oncogene, 2009)
The mixed-lineage leukemia (MLL) family of histone methyltransferases has become notorious for the participation of the founding member, MLL, in fusion proteins that cause acute leukemia. Despite structural conservation, no other MLL homolog has so far been found in a similar arrangement. Here, we show that fusion proteins based on Mll2, the closest relative of MLL, are incapable of transforming hematopoietic cells. Elaborate swap experiments identified the small CxxC zinc-binding region of Mll2 and an adjacent 'post-CxxC' stretch of basic amino acids as the essential determinants for the observed difference. Gel shift experiments indicated that the combined CxxC and post-CxxC domains of MLL and Mll2 possess almost indistinguishable DNA-binding properties in vitro. Within the cellular environment, however, these motifs guided MLL and Mll2 to a largely nonoverlapping target gene repertoire, as evidenced by nuclear localization, reporter assays, and measurements of homeobox gene levels in primary cells expressing MLL and Mll2 fusion proteins. Therefore, the CxxC domain appears to be a promising target for therapies aimed at MLL fusion proteins without affecting the general function of other MLL family members. © 2009 Macmillan Publishers Limited All rights reserved.
Keywords: CxxC domain; MLL; MLL2; Transformation